2018
DOI: 10.1142/s0219581x18500072
|View full text |Cite
|
Sign up to set email alerts
|

Siver Nanoparticles Toxicity in Brine Shrimp and its Histopathological Analysis

Abstract: Silver nanoparticles (Ag NPs) are interesting nanotechnology materials with borderless applications in medical science, environmental science, material science and are also used in various kinds of industrial household products. Increasing usage of Ag NPs every year leads to increased risk of nanomaterial contamination in the environment, especially natural water sources with harmful effects in aquatic animals, and to ecosystem disruption. In the present study, Ag NPs toxicity was determined using brine shrimp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In a study on the crustacean A. salina , synthetic AgNPs smaller than 100 nm in size exhibited a LC 50 of approximately 3.5 mg L −1 . 31 Similarly, synthetic AgNPs with an average size of 33–44 nm produced using Sargassum ilicifolium , as well as commercial and synthetic AgNPs with a size of 30–40 nm, demonstrated a LC 50 of 10 nM after 48 h on this same species. 43,44 The commercial AgNPs caused DNA damage, increased nauplius, aggregation in the intestinal region, and apoptosis, while the percentage of hatching in cysts of A. salina was decreased.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In a study on the crustacean A. salina , synthetic AgNPs smaller than 100 nm in size exhibited a LC 50 of approximately 3.5 mg L −1 . 31 Similarly, synthetic AgNPs with an average size of 33–44 nm produced using Sargassum ilicifolium , as well as commercial and synthetic AgNPs with a size of 30–40 nm, demonstrated a LC 50 of 10 nM after 48 h on this same species. 43,44 The commercial AgNPs caused DNA damage, increased nauplius, aggregation in the intestinal region, and apoptosis, while the percentage of hatching in cysts of A. salina was decreased.…”
Section: Discussionmentioning
confidence: 92%
“…It is worth noting that mussels are more sensitive than P. pandaliformis, and the latter is more sensitive than zebrafish D. rerio, underscoring the need for assessing toxicity in multiple species to obtain a comprehensive understanding of the potential impact of these nanoparticles. 13 Furthermore, other studies in the literature have reported the toxicity of AgNPs to various species, including Artemia salina, 31 crustaceans such as Daphnia pulex, Daphnia galeata, and Daphnia magna, [32][33][34][35] the Australian freshwater shrimp Paratya australiensis, 36 the Japanese medaka fish Oryzias latipes, [37][38][39] the fathead minnow Pimephales promelas, 40,41 and the silver carp Hypophthalmichthys molitrix. 42 In a study on the crustacean A. salina, synthetic AgNPs smaller than 100 nm in size exhibited a LC 50 of approximately 3.5 mg L −1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many shedding cells are seen in the tubule lumen, and melanization-producing hemocytes are extensively infiltrated around the tubules. [37] Reporting on the LC50 test using a specific dosage of silver nanoparticles on brine shrimp showed necrosis in intestinal cells. The percentage of damage caused by each treatment varies.…”
Section: Histopathological Analysismentioning
confidence: 99%